Moderating Role of Perceived Job Alternatives in the Relationships between Individual Learning, Compensation, Overtime Work and Turnover Intention - Naimat Maqsood; Waqas Farooq; Imran Akbar; Ishfaq Ahmed (Journal of Management Practices, Humanities and Social Sciences, 2023)
Employee turnover is a significant concern for Information Technology (IT) organizations. Therefore, this paper aims to examine the moderating role of perceived job alternatives in the relationship between individual learning, compensation and benefits, and overtime work, on the turnover intention of employees. A cross-sectional survey was conducted to collect the data through a selfadministered structured questionnaire from 524 employees working in various micro, small, medium, and large size IT organizations. Data was analyzed using frequency, alpha reliability, common method biases, and process macro Hayes model 1. The results indicate that employees' turnover intention reduces due to individual learning, compensation and benefits, and overtime work. Moreover, perceived job alternatives only moderate the relationships between individual learning and compensation and benefits. This study advances the literature on employee turnover intention both theoretically and empirically, with a focus on perceived job alternatives as a moderator. Future directions and limitations were also discussed.